Optimalisasi Layanan Bimbingan Konseling Inklusif sebagai Upaya Peningkatan Kesejahteraan Sosial Masyarakat Desa Bongo - Hasan, Moh Alwi; Muslim, Mohamad Riadi; Baid, Mohamad Fikri; Siregar, Ilham Khairi (CERED Indonesia Publishing, 2025)
Bongo Village faces socio-psychological challenges such as juvenile delinquency, low mental health literacy, and limited access to counseling services. This community engagement program aims to optimize inclusive counseling services to improve social well-being. Activities were carried out in four stages: preparation (observation and needs assessment), implementation (door-to-door outreach, youth counseling, and community outbound), evaluation (formative and summative), and follow-up (formation of a Village Counseling Task Force and reflective discussions). The program employed participatory methods and adventure-based counseling, emphasizing active community involvement. Results show increased psychosocial literacy, intergenerational participation, and the establishment of the Village Counseling Task Force (K3D) as a sustainable outcome. These findings demonstrate that inclusive, community-based counseling services effectively strengthen social cohesion, reduce stigma toward mental health support, and are feasible for replication in other rural areas.